Profil Hormon Progesteron pada Anjing Kintamani Fase Anestrus Setelah Disuntik Pregnant Mare Serum Gonadotrophin (THE PROGESTERONE PROFILE IN ANESTRUS KINTAMANI BITCHES AFTER INJECTED USING PREGNANT MARE SERUM GONADOTROPIN) - Puja, I Ketut (Jurnal Veteriner; Vol 2 No 2 (2001), 2016)
Profil Hormon Progesteron pada Anjing Kintamani Fase Anestrus Setelah Disuntik Pregnant Mare Serum Gonadotrophin (THE PROGESTERONE PROFILE IN ANESTRUS KINTAMANI BITCHES AFTER INJECTED USING PREGNANT MARE SERUM GONADOTROPIN)
Keywords: PMSG, HSG, progesterone, Kintamani bitches